Employer’s Efficiency In E-Ktp Services In The City Of Cimahi - Rahmawati, Yustika; Kurhayadi, Kurhayadi; Susanty, Aty (SEIKO : Journal of Management & Business, 2023)
This study analyzes the effectiveness of the performance of officials in the e-KTP creation service in the Civil Records and Population Service of Cimahi City. Through a quantitative approach, primary and secondary data are collected to identify factors that affect staff performance. The results showed that the level of staff expertise, the availability of resources, the use of information technology, and management support influence service efficiency. Improvement efforts include staff training, improved access to resources, information technology development, and better service management. This researcher provides insights to improve public satisfaction and work efficiency in the Department of Population and Civil Records of Cimahi City. Keywoard: employee achievement, service efficiency, e-KTP